Immunogenetics: Methods and Applications in Clinical Practice - Christiansen, Frank T.; Tait, Brian D. (Methods in molecular biology, 2012)
The Major Histocompatibility Complex - A Paradigm for Studies of the Human Genome -- HLA Typing by SSO and SSP Methods -- Methods for Diagnostic HLA Typing in Disease Association and Drug Hypersensitivity -- HLA Typing Using Bead Based Methods -- HLA Typing by Direct DNA Sequencing -- Data Analysis of HLA Sequencing using Assign-SBT v3.6+ from Conexio -- Simple Methods for the Detection of HLA-G Variants in Coding and Non-Coding Regions -- Molecular Typing of HLA-E -- Molecular Analysis of Complement Component C4 Gene Copy Number -- Genotyping of Single Nucleotide Polymorphisms (SNPs) by 5' Nuclease Allelic Discrimination -- High Resolution MICA Genotyping by Sequence-Based Typing (SBT) -- Standard Methods for the Management of Immunogenetic Data -- Analytical Methods for Immunogenetic Population Data -- Analytical Methods for Disease Association Studies with Immunogenetic Data -- Impact of HLA Matching and HLA Antibodies in Organ Transplantation: a Collaborative Transplant Study View -- Screening for Antibodies Against MICA by Luminex Flow Cytometry -- HLA Antibody Detection and Characterization by Solid Phase Immunoassays - Methods and Pitfalls -- Detection and Characterisation of Alloreactive T Cells -- Detection of Allo-HLA Crossreactivity by Viral Specific Memory T-Cell Clones using Single HLA Transfected K562 Cells -- Separation and Cryopreservation of Lymphocytes from Spleen and Lymph Node -- Crossmatching by Complement-Dependent Lymphocytotoxicity (CDC) -- The Lymphocyte Crossmatch by Flow Cytometry for Kidney Transplantation -- Overview of the Killer Cell Immunoglobulin-Like Receptor (KIR) System -- KIR Typing by Non Sequencing Methods: Polymerase-Chain Reaction with Sequence-Specific Primers (PCR-SSP) -- Killer Cell Immunoglobulin-Like Receptors (KIR) Typing by DNA Sequencing -- An Overview of Methods Required to Evaluate Donor NK Cell Alloreactivity for Haploidentical Haemopoietic Stem Cell Transplantation -- The Detection of NK Cell Alloreactivity by Flow Cytometric CD107a Assay -- Clinical Production and Therapeutic Applications of Alloreactive Natural Killer Cells -- Minor Histocompatibility Antigen Typing by DNA Sequencing for Clinical Practice in Hematopoietic Stem-Cell Transplantation -- Donor Registries and Search Strategies -- Cytokine Gene Polymorphisms: Methods of Detection and Biological Significance -- IMGT® Tools for the Nucleotide Analysis of Immunoglobulin (IG) and T Cell Receptor (TR) V-(D)-J Repertoires, Polymorphisms, and IG Mutations: IMGT/V-QUEST and IMGT/HighV-QUEST for NGS -- IMGT/DomainGapAlign: the IMGT® Tool for the Analysis of IG, TR, MH, IgSF and MhSF Domain Amino Acid Polymorphism -- Human Gm, Km and Am Allotypes and their Molecular Characterization: a Remarkable Demonstration of Polymorphism.